Hubungan Antara Kadar D-Dimer dengan Angka Mortalitas pada Pasien Dewasa Terkonfirmasi Coronavirus Disease 19 di RSUD Abdul Moeloek Bandar Lampung Periode Tahun 2020 – 2021.docx - Attila Firjatullah, Muhammad Daffa; Tjiptaningrum, Agustyas; Putri, Giska Tri (CV. Jasa Sukses Abadi, 2024)
Lampung is one of the regions with the highest Case Fatality Rate (CFR) in Indonesia, which was 7.7% on September 16, 2021. Several studies have shown that D-Dimer levels influenced the mortality of confirmed Covid-19 patients. This study aimed to analyze the correlation between D-Dimer levels and the mortality rate of confirmed Covid-19 adult patients. This research was an observational analytic study using a cross-sectional approach. The population of this study was all confirmed covid-19 adult patients who fulfilled the inclusion and exclusion criteria in Abdul Moeloek Hospital Medical Record Installation from 2020 to 2021. The samples were taken using simple random technique. Data collected were D-Dimer level, mortality rate, and patient’s personal information. Data were analyzed by Chi-Square using statistical data processing program. There were 94 subjects admitted in our study, divided into groups of survivors and non-survivors. From the non-survivors’ group, 43 (91%) subjects had a high D-Dimer level. The Chi-Square analysis showed a correlation between D-Dimer levels and the mortality rate of Covid-19 patients (p-value = 0,001). Statistically, there was a significant correlation between D-Dimer levels and the mortality rate of confirmed Covid-19 patients.